giorgiana1976 | Student

We'll have to apply the following identity to prove the given expression:

sin(a-b) = sin a*cos b - sin b*cos a

Let a = `pi` /2 and b = x

sin (`pi` /2 - x) = sin `pi` /2*cos x - sin x* cos `pi` /2

But sin `pi` /2 = 1 and cos `pi` /2 = 0

sin (`pi` /2 - x) = 1*cos x - sin x*0

sin (`pi` /2 - x) = cos x

Therefore, the given expression sin (`pi` /2 - x) = cos x represents an identity.

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question